Analisis statik kekuatan struktur pesawat UAV vertical take off-landing VX-2 - Djarot Wahju Santoso; Wawan Edi Saputra (SENATIK STT Adisutjipto, 2020)
VTOL UAV aircraft is aircraft capable of vertical takeoff and landing (VTOL) and have flexible maneuverability. This aircraft is increasingly being used because of its ability to carry out various missions. The aircraft modification process that was previously designed for the VTOL VX-1 was carried out to correct problems encountered during flight tests The stages of research carried out in the static analysis of the structural strength of the UAV VX-2 aircraft were to modify the wing structure, fuselage and tail of the previous aircraft design, carry out modeling with CATIA software and then analyze the structure with Patran-Nastran to ensure the modification was safe. The result of the analysis the modified structure of the UAV VX-2 aircraft design, the wing structure has a maximum stress 185 MPa in the case of torsion loads, while the maximum tension tail structure 257 MPa is located in the horizontal stringer stabilizer at pull up loads. The results of the calculation the Margin of Safety with all positive values, the modified structure is declared safe.